Association of Iron Deficiency Anemia and Breastfeeding in Children - Javed, Sumaiya; Ghafoor, Tariq; Khan, Qamar-Uz-Zaman; Ikram, Farooq; Tahir, Muhammad; Naz, Shagufta (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the frequency and association of iron deficiency anemia in breastfed children less than equal to six months of age.Study Design: Prospective observational studyPlace And Duration of Study: Pak Emirate Military Hospital & CMH, Rawalpindi Pakistan from Sep 2020 to Mar 2021Methodology: All children less than equal to 6 months of age of either sex having birth parameters of term gestation (between 37 and 42 weeks), birth weight 2500 grams or more, uneventful postnatal course were consecutively enrolled. Iron deficiency anemia was defined based on serum ferritin concentration